Islam dan Negara Menurut M. Natsir dan Abdurrahman Wahid - Saoki, Saoki (al-Daulah: Jurnal Hukum dan Perundangan Islam, 2014)
Abstract: This article discusses M. Natsirâs and Abdurrahman Wahidâs thought about the relationship between Islam and state. Both of M. Natsir and Abdurrahman Wahid agree that the most realistic system to be applied in Indonesia is a democratic system. They also agree that there is no a rigid political system in Islam as it has existed today. In addition, Islam provides the basic principles of the nation and state namely deliberation, justice, equality, freedom, and togetherness. The fundamental difference between M. Natsirâs Â and Gus Durâs thought in viewing the relationship between Islam and state isÂ  about the two things: first, their respond to secularism, which tries to separate between religion and state; and second, their political thought in addressing democracy and the Pancasila ideology as the fundamental principles of Indonesia.Keywords: Islam, state, M. Natsir, Abdurrahman Wahid.